A Cooperative Radar System With Active Reference Target Synchronization for Kinematic Target Analysis - Edstaller, Stefan; Mueller, Dominik (IEEE Transactions on Microwave Theory and Techniques, 2021)
This article presents a short-range cooperative radar system in the 77-GHz band for the estimation of kinematic parameters, such as position, velocity, and acceleration of a target. The proposed system uses two FMCW radar sensors that are operated incoherently and only depend on a common trigger for coarse synchronization. The resulting frequency offset and phase offset in the beat spectrum of the radar sensors are eliminated through calibration with a known active reference target. For easy detection of the reference target in the beat spectrum, a novel interchirp modulation method is proposed. The sampled data of a single receive channel of only one of the sensors of the system allow for a complete estimation of the kinematic target parameters. The theoretical analysis of incoherent FMCW radar systems is carried out, and the constraints and signal processing algorithms are derived from the results. The theory and operating principle of the proposed system are verified through measurements in an anechoic chamber. The accuracies for the position, velocity, and direction of movement (DoM) estimation are better than 10 mm, 0.03 m/s, and 1.4°, respectively.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Bistatic radar; cooperative systems; millimeter-wave radar; position measurement; radar applications; radar detection; radar signal processing; radar theory; radar tracking; velocity measurement.